Bio-efficacy of Ready-mix Herbicide on Weed Flora and Productivity of Transplanted Rice - Pramanik, Kalipada; Shah, Maksud Hasan; Gupta, Rahul Kumar; Singhal, Mayank (International Journal of Bio-resource and Stress Management, 2020)
A field experiment was conducted during 2017 and 2018 at Agricultural Farm, Institute of Agriculture, Visva-Bharati, West Bengal, India to evaluate the bio-efficacy of ready-mix herbicide in transplanted rice. The experiment consisting of ten treatments was laid out in randomized bloc design with three replications. The crop field was infested complex weed flora: grasses likeEchinochloa crus-galli and Panicum repens sedges like Cyperus iria, Cyperus difformis, Fimbristylis miliacae and Cyperus rotundus and broad leaved weeds like Eclipta alba, Ludwigia parviflora, Marsilea quadrifolia and Monochoria vaginalis. The results revealed that ready-mix application of fenoxaprop 5%+Chlorimuron 0.6%+Pretilachlor 50% ME at 1200 and 1000 ml ha-1 gave higher weed control index of 84.90% and 81.60% against grassy weeds, 84.09% and 82.95% against broad leaved weeds and 81.89% and 79.79% against sedges during 2017 and 84.18% and 82.95% against grassy weeds, 80.04% and 80.84% against broad leaved weeds and 82.33% and 79.57% against sedges during 2018. Both doses of fenoxaprop+chlorimuron+pretilachlor was better than chlorimuron ethyl, fenoxaprop-p-ethyl, pretilachlor and pyrazosulfuron ethyl. Fenoxaprop+Chlorimuron+Pretilachlor 1200 ml ha-1and 1000 ml ha-1 resulted into the higher number of panicles m-2, test weight and grain yield (6088 and 6058 kg ha-1 in 2017 and 6513 and 6490 kgha-1 in 2018). Both were superior to its lower doses (800 ml ha-1) and chlorimuron ethyl, fenoxaprop-p-ethyl, pretilachlor and pyrazosulfuron ethyl during both the years. Weeds allowed to grow throughout the crop season reduced thegrain yield to the extent of 32.2 and 35.5% during 2017 and 2018, respectively.